Rediscovering the value of images in supporting personal identification of missing migrants. (February 2022) - Cappella, Annalisa; De Angelis, Danilo; Mazzarelli, Debora; Vitale, Albarita; Caccia, Giulia; Fracasso, Tony; Cattaneo, Cristina
Highlights: A descriptive study of antemortem photographic materials of missing migrants. The quantity and quality of AM images provided by relatives of missing migrants. Unavailability of classical AM data for identification of dead migrants. Images may turn out to be fundamental and sometime the only resort for identification. Abstract: The crisis concerning the identification of dead migrants is forcing forensic scientists to deal with the unavailability of classical antemortem (AM) data such as radiological information and DNA. However many times there is abundant AM photographic data of which the availability and quality is underestimated. Independently of when facial image comparison can be used as a valid identification method, description of the unexpected quality and quantity of images in the scenario of unidentified migrant decedents is given in this observational study. It focuses on the overall characteristics of the AM images available for a group of 74 missing migrants related to the disaster of October 3rd, 2013. 394 images were collected: an average of 6 for each missing person. 18% are original pictures, 47.5% scans of original images, 9.9% scans of printed images while 9.4% downloaded from social networks such as Facebook. 42.7% of images resulted in focus. Among all the images, about the 10% has been used in the personal identification process to ascertain the identity of 22 persons, because of the visibility of identifying details (facial, dental and body features). The importance of such a finding should not be diminished by its simplicity. Today, those involved in collecting AM information from relatives of dead migrants are underestimating the possible presence of images, even in sub-Saharan populations, where, contrary to belief and data, technology, though simple, is available and images may turn out to be abundant and useful (and at times the only resort) for identification.